2012
DOI: 10.1097/mph.0b013e3182408412
|View full text |Cite
|
Sign up to set email alerts
|

Foamy Histiocytes in a Child With Acute Myeloid Leukemia

Abstract: Here, we have reported foamy histiocytes noticed in the bone marrow aspiration (BMA) smears of a 14-year-old girl with the diagnosis of AML after she received 2 weeks of chemotherapy. We suggest that after the intensive chemotherapy, degradation products of blasts phagocytosed by the histiocytes may have been the cause in the increase in such histiocytes before regeneration of the bone marrow. After the remission was achieved, foamy histiocytes disappeared from BMA smears. These foamy histiocytes may be an idi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Foamy histiocytes are usual in a variety of disorders such as metabolic and/or lysosomal storage disorders as well as prolonged total parenteral nutrition [ 1 , 2 ]. Post-chemotherapy foamy histiocytes have been reported only twice in bone marrow aspiration (BMA) smears according to our investigation, in one case of acute myeloid leukemia and one case of metastatic adenocarcinoma of the prostate [ 3 , 4 ]. Here we report a new case of post-chemotherapy foamy histiocytes in BMA smears.…”
Section: To the Editormentioning
confidence: 81%
See 1 more Smart Citation
“…Foamy histiocytes are usual in a variety of disorders such as metabolic and/or lysosomal storage disorders as well as prolonged total parenteral nutrition [ 1 , 2 ]. Post-chemotherapy foamy histiocytes have been reported only twice in bone marrow aspiration (BMA) smears according to our investigation, in one case of acute myeloid leukemia and one case of metastatic adenocarcinoma of the prostate [ 3 , 4 ]. Here we report a new case of post-chemotherapy foamy histiocytes in BMA smears.…”
Section: To the Editormentioning
confidence: 81%
“…That report suggested that the foamy histiocytes were related to degradation products of blasts phagocytized by the histiocytes. This finding might also be an idiosyncratic response to the chemotherapy [ 3 ]. In conclusion, a history of intensive chemotherapy should be considered in the list of differential diagnoses of foamy histiocytes in bone marrow specimens.…”
Section: To the Editormentioning
confidence: 99%